Clinical and immunological insights into SARS-CoV-2 reinfection: a propensity score-matched cohort study - Chenxi Zhao; Lu Liu; Ziruo Ge; Jingxia Wang; Ranran Wang; Zhouling Jiang; Di Tian; Zhihai Chen (BMC Infectious Diseases)
Abstract Background The global circulation of SARS-CoV-2 has led to an increasing number of reinfections, raising concerns about their clinical and immune consequences. Understanding the differences in disease severity, vaccination impact, and immune response between primary infections and reinfections is essential for guiding public health strategies. Methods We conducted a retrospective cohort study of hospitalized COVID-19 patients at Beijing Ditan Hospital from January 2023 to June 2024. SARS-CoV-2 reinfection cases were matched 1:2 with primary infection cases using nearest neighbor propensity score matching (PSM) to balance age, sex, and comorbidities between the groups. Clinical characteristics, laboratory findings, serum antibody levels, lymphocyte subsets, and the impact of vaccination on disease severity were analyzed. Results A total of 907 patients were included, comprising 821 with primary infection and 86 with reinfection. After matching, 131 cases remained in the primary infection group and 75 in the reinfection group. No significant differences were observed in disease severity, mortality, or most clinical symptoms. Trend analysis revealed that an increasing number of vaccine doses was significantly associated with a decreasing trend in severe disease in both the primary infection group (P = 0.0221) and the reinfection group (P = 0.0449). IgG levels were significantly higher in reinfected patients (P < 0.001), whereas IgM levels showed no significant difference (P = 0.474). Among patients with primary infection, severe cases exhibited lower T cell counts than non-severe cases (P < 0.001), but no significant differences in T cell subsets were observed between non-severe and severe reinfections. Conclusions The higher IgG levels in reinfected individuals suggest a robust immune memory response, while T cell depletion plays a crucial role in severe primary infections. Vaccination provided a protective effect against severe disease in both primary and reinfected individuals, with a significant decreasing trend in severe/critical cases as the number of vaccine doses increased.